Development of a Microcontroller-based Wireless Accelerometer for Kinematic Analysis - Maria Clarissa Alvarez Carasco; Jan Pierre Potato Pizarro; Giovanni Alarkon Tapang (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
Wireless sensor networks (WSNs) allow real-time measurement and monitoring with less complexity and more efficient in terms of obtaining data when the subject is in motion. It eliminates the limitations introduced by wired connections between the sensors and the central processing unit. Although wireless technology is widely used around the world, not much has been applied for education. Through VISSER, a low cost WSN using nRF24L01+ RF transceiver that is developed to observe and analyze the kinematics of a moving object is discussed in this paper. Data acquisition and transmission is realized with the use of a low power and low cost microcontroller ATtiny85 that obtains data from the ADXL345 three-axis accelerometer. An ATtiny85 also controls the receiving module with a UART connection to the computer. Data gathered are then processed in an open-source programming language to determine properties of an object’s motion such as pitch and roll (tilt), acceleration and displacement. This paper discusses the application of the developed WSN for the kinematics analysis of a toy car moving on flat and inclined surfaces along the three axes. The developed system can be used in various motion detection and other kinematics applications, as well as physics laboratory activities for educational purposes.